Effect of silk nano‐disc dispersion on mechanical, thermal, and barrier properties of poly(lactic acid) based bionanocomposites. Issue 38 (30th July 2018) - Patwa, Rahul; Kumar, Amit; Katiyar, Vimal
ABSTRACT: Exacerbated environmental concerns about petroleum‐based plastics provide the impetus to foster sustainable poly(lactic acid) (PLA) based food packaging. Nonetheless, PLA has its foibilities such as its brittleness, higher gas permeability, and slow crystallization. With the intent to mitigate the above shortcomings, we report a maiden effort for the fabrication of PLA/crystalline silk nano‐discs (CSNs) based bionanocomposites by melt‐extrusion for high temperature engineering and food packaging applications. Acid hydrolyzed silk fibroin from muga silk ( Antheraea assama ) yields CSNs, a crystalline hydrophobic discotic nanofiller with diameter of ∼50 nm and thickness ∼3 nm. At optimum loadings of 1 wt % uniform dispersed CSNs with percolated network structures covering the entire matrix can be seen. Due to enhanced crystal nucleation density, water vapor, and oxygen permeability reduced by ∼30% and ∼70%, respectively. Enhancement in toughness, percentage elongation, and tensile strength up to ∼65%, ∼40%, and ∼10%, respectively, is obtained. Onset of thermal decomposition for the PLA/CSN improved ∼10 °C, confirming the role of CSN in enhancing melt stability. Accordingly, this investigation renders a novel non‐invasive approach for increasing the crystallinity with improvement in thermomechanical and barrier properties which make this bionanocomposite, a promising candidate for food packaging applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46671. Abstract :